2018
DOI: 10.7717/peerj.5937
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between vertical and horizontal force-velocity-power profiles in various sports and levels of practice

Abstract: This study aimed (i) to explore the relationship between vertical (jumping) and horizontal (sprinting) force–velocity–power (FVP) mechanical profiles in a large range of sports and levels of practice, and (ii) to provide a large database to serve as a reference of the FVP profile for all sports and levels tested. A total of 553 participants (333 men, 220 women) from 14 sport disciplines and all levels of practice participated in this study. Participants performed squat jumps (SJ) against multiple external load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
131
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(160 citation statements)
references
References 41 publications
23
131
3
3
Order By: Relevance
“…The differences in sprinting acceleration performance between sprinters and hurdlers may be more explained by differences in the mechanical effectiveness of force application between the events and especially by the ability to apply more effectively the force into the anteroposterior direction. These results are in agreement with previous studies that have revealed that highlevel athletes are able to horizontally apply higher forces upon contact with the ground (Morin et al, 2011;Buchheit et al, 2014;Kawamori et al, 2014;Pantoja et al, 2016;Jiménez-Reyes et al, 2018b).…”
Section: Discussionsupporting
confidence: 93%
“…The differences in sprinting acceleration performance between sprinters and hurdlers may be more explained by differences in the mechanical effectiveness of force application between the events and especially by the ability to apply more effectively the force into the anteroposterior direction. These results are in agreement with previous studies that have revealed that highlevel athletes are able to horizontally apply higher forces upon contact with the ground (Morin et al, 2011;Buchheit et al, 2014;Kawamori et al, 2014;Pantoja et al, 2016;Jiménez-Reyes et al, 2018b).…”
Section: Discussionsupporting
confidence: 93%
“…The potential applications are numerous, within the training, talent identification or injury management fields, as observed in recent studies using the concept of sprint acceleration force-velocity profiling (e.g. Haugen et al, 2020b;Jiménez-Reyes et al, 2018, 2020Mendiguchia et al, 2014Mendiguchia et al, , 2016. The reliability observed between Phase1 and Phase2 (random error <8%, Table 1) is very good and in line with reliability observed during standardized sprint testing (Haugen et al, 2020a;Samozino et al, 2016).…”
Section: Discussionsupporting
confidence: 75%
“…These findings are supported not only by the fact that jump height was correlated to Vmax, but also because unresisted and RST times (i.e., T 30-20BM, T 30-40BM, T 30-60BM, T 30-80BM) were strongly correlated to both jumping tasks and Vmax. In contrast, a recent study in elite rugby players [19] reported no significant correlations between sprint times and jump height. The most noticeable difference between sprinting and jumping is that the former requires the resultant force and power to be more horizontally directed, while the latter requires a vertical orientation of the abovementioned variables [35].…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, a recent study reported that isometric mid-thigh pull (IMTP) variables are significantly associated with strength, agility, and sprint in rugby union players [2,18]. In contrast, the authors of [19] reported non-significant correlations between the squat jump (jump height) and 20 m sprint times in male and female rugby players. Nevertheless, it is clear that force production is an integral component to maximal sprinting velocity [20,21].…”
Section: Introductionmentioning
confidence: 99%